PENGEMBANGAN BAHAN AJAR IPA BERBASIS TPACK DI SEKOLAH DASAR PERIODE 2018-2024 - Inggit Prasetyo Utami; Yeri Sutopo; Agus Yuwono; Bambang Subali; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Current technological developments have a significant impact on education, especially in the preparation of teaching materials that support 21st century skills, namely the critical thinking aspect. One of the relevant approaches is the application of the TPACK (Technological Pedagogical Content Knowledge) framework in the development of teaching materials. TPACK integrates technology, pedagogy, content and knowledge to create interactive and relevant learning. This study aims to review the use of TPACK in science teaching materials in elementary schools and how its application affects students' critical thinking skills. Using the Systematic Literature Review (SLR) method, the researcher identified 25 articles from 2018 to 2024, which are relevant to the theme of developing TPACK-based science teaching materials. Based on the results of the analysis, it is shown that TPACK-based teaching materials are effective in improving students' understanding of scientific concepts. From various studies, it is proven that the TPACK model can support and enrich learning through the use of interactive digital media. Based on the description above, it can be concluded that the development of TPACK-based teaching materials in basic education can improve the quality of science learning and improve students' critical thinking skills.